2021
DOI: 10.3390/app11104645
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis and Taguchi-Based Optimization of the Thermohydraulic Performance of a Solar Air Heater Duct Baffled on a Back Plate

Abstract: In this paper, a solar air collector duct equipped with baffles on a back plate was numerically investigated. The Reynolds number (Re) was varied from 5000 to 20,000, the angle baffle (a) from 30° to 120°, the baffle spacing ratio (Pr) from 2 to 8, and the baffle blockage ratio (Br) from 0.375 to 0.75 to examine their effects on the Nusselt number (Nu), the friction factor (f), and the thermohydraulic performance parameter (η). The 2D numerical simulation used the standard k-ε turbulence model with enhanced wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Heat transfer improvement between the airflow and absorption plate of a SAH is a topic of constant interest to researchers. Inserts including rib roughness, fins, porous media, or baffles in the SAH duct have led to increases in the heat transfer rate due to the elimination of the laminar sub-layer close to the absorber plate and airflow reconfiguration [2,3]. The small convection heat transfer coefficient of the air leads to a high absorber plate temperature, resulting in a large top heat loss of the SAH.…”
Section: Introductionmentioning
confidence: 99%
“…Heat transfer improvement between the airflow and absorption plate of a SAH is a topic of constant interest to researchers. Inserts including rib roughness, fins, porous media, or baffles in the SAH duct have led to increases in the heat transfer rate due to the elimination of the laminar sub-layer close to the absorber plate and airflow reconfiguration [2,3]. The small convection heat transfer coefficient of the air leads to a high absorber plate temperature, resulting in a large top heat loss of the SAH.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [13] compared square wave ribs and multiple broken ribs, and showed that the multiple broken ribs had superior heat transfer and lower friction penalty in comparison to the square wave ribs. Thao et al [14] conducted a numerical investigation of an SAH coupled with inclined baffles and optimized the installation conditions of the baffles using the Taguchi method. Bhuvad et al [15] proposed a novel type of absorber plate roughened with apex-up discrete arc ribs, and compared the thermal performance achieved by the proposed ribs with those of the existing apex-down ribs.…”
Section: Introductionmentioning
confidence: 99%
“…The baffle or partition inside the channels and cavities plays an important role in convective flow under various situations [26][27][28][29]. Mahapatra et al [30] discovered the opposite combined convective stream in a partitioned box with two partitions attached in the bottom and top walls.…”
Section: Introductionmentioning
confidence: 99%